Boron isotope composition of geothermal fluids and borate minerals from salar deposits (central Andes/NW Argentina) - Kasemann, Simone A. (2004)
We have measured the boron concentration and isotope composition of regionally expansive borate deposits and geothermal fluids from the Cenozoic geothermal system of the Argentine Puna Plateau in the central Andes. The borate minerals borax, colemanite, hydroboracite, inderite, inyoite, kernite, teruggite, tincalconite, and ulexite span a wide range of d 11B values from 229.5 to 20.3‰, whereas fluids cover a range from 218.3 to 0.7‰. The data from recent coexisting borate minerals and fluids allow for the calculation of the isotope composition of the ancient mineralizing fluids and thus for the constraint of the isotope composition of the source rocks sampled by the fluids. The boron isotope composition of ancient mineralizing fluids appears uniform throughout the section of precipitates at a given locality and similar to values obtained from recent thermal fluids. These findings support models that suggest uniform and stable climatic, magmatic, and tectonic conditions during the past 8 million years in this part of the central Andes. Boron in fluids is derived from different sources, depending on the drainage system and local country rocks. One significant boron source is the Paleozoic basement, which has a whole-rock isotopic composition of d 11B ¼ 28.9 ^ 2.2‰ (1 SD); another important boron contribution comes from Neogene-Pleistocene ignimbrites (d 11B ¼ 23.8 ^ 2.8‰, 1 SD). Cenozoic andesites and Mesozoic limestones (d 11B # þ 8‰) provide a potential third boron source.